RETROSPECTIVE AND COMPARATIVE STUDY OF 42 CASES OF ANEMIA IN DOGS - Daniela Mihaela Neagu; Vlad Luca; Răzvan Codea; Cristian Popovici; Alexandra Biriș (Agricultura)
Anemia is a common pathology in dogs, characterized by a decrease in red blood cells 16 or hematocrit concentration, leading to a reduction in the blood's ability to carry oxygen. Anemia in dogs is a multifactorial condition requiring a detailed diagnostic approach and treatment tailored to each individual case. A better understanding of the causes and treatments of anemia can significantly improve the quality of life of affected dogs and reduce the mortality associated with this condition. This thesis aims to explore the different causes based on scientific literature reviews and the analysis of clinical cases collected within the emergency hospital of the Faculty of Veterinary Medicine in Cluj-Napoca. Data were collected and interpreted to determine trends 24 and correlations between different types of anemia and their underlying causes. The results of the study revealed several causes of anemia, being classified as hemorrhages: by intoxication, trauma or postoperative hemorrhages; hemolysis: autoimmune, parasitic; and production deficits: mainly following chronic renal failure.